Human leukocyte antigen class II DQB1*0301, DRB1*1101 alleles and spontaneous clearance of hepatitis C virus infection: A meta-analysis - Hong, Xin (World J Gastroenterol, 2005)
AIM: To assess the associations of human leukocyte antigen (HLA) class II DQB1*0301 and/or DRB1*1101 allele with spontaneous hepatitis C virus (HCV) clearance by meta-analysis of individual dataset from all studies published till date. METHODS: To clarify the impact of HLA class II polymorphisms on viral clearance, we performed a meta-analysis of the published data from 11 studies comparing the frequencies of DQB1*0301 and DRB1*1101 alleles in individuals with spontaneous resolution to those with persistent infection. As we identified the heterogeneity between studies, summary statistical data were calculated based on a random-effect model. RESULTS: Meta-analyses yielded summary estimates-odds ratio (OR) of 2.36 [95%CI (1.62, 3.43), P<0.00001] and 2.02 [95%CI (1.56, 2.62), P<0.00001] for the effects of DQB1*0301 and DRB1*1101 alleles on spontaneous clearance of HCV, respectively. CONCLUSION: These results support the hypothesis that specific HLA class II alleles might influence the susceptibility or resistance to persistent HCV infection. Both DQB1*0301 and DRB1*1101 are protective alleles and present HCV epitopes more effectively to CD4(+)T lymphocytes than others, and subjects with these two alleles are at a lower risk of developing chronic HCV infection. Large, multi-ethnic confirmatory and well-designed studies are needed to determine the host genetic determinants of HCV infection.